Medical students' professional identity development from being actors in an objective structured teaching exercise. (2nd November 2018) - De Grasset, Jehanne; Audetat, Marie-Claude; Bajwa, Nadia; Jastrow, Nicole; Richard-Lepouriel, Hélène; Nendaz, Mathieu; Junod Perron, Noelle
Abstract: Introduction: Medical students develop professional identity through structured activities and impromptu interactions in various settings. We explored if contributing to an Objective Structured Teaching Exercise (OSTE) influenced students' professional identity development. Methods: University clinical faculty members participated in a faculty development program on clinical supervision. Medical students who participated in OSTEs as simulated residents were interviewed in focus groups about what they learnt from the experience and how the experience influenced their vision of learning and teaching. Transcripts were analyzed using the Goldie's personality and social structure perspective model. Results: Twenty-five medical students out of 32 students involved in OSTEs participated. On an institutional level, students developed a feeling of belonging to the institution. At an interactional level, students realized they could influence the teaching interaction by actively seeking or giving feedback. On the personal level, students realized that errors could become sources of learning and felt better prepared to receive faculty feedback. Conclusion: Taking part in OSTEs as a simulated resident has a positive impact on students' vision regarding the institution as a learning environment and their own role by actively seeking or giving feedback. OSTEs support their professional identity development regarding learning and teaching while sustaining faculty development.